Enhancing the capacity of supercapacitive swing adsorption CO2 capture by tuning charging protocols. Issue 22 (26th May 2022) - Binford, Trevor B.; Mapstone, Grace; Temprano, Israel; Forse, Alexander C.
Abstract : Electrochemical carbon dioxide capture by supercapacitors is found to depend strongly on charging protocols. Varying the charging polarity leads to increases in capture capacities and improved mechanistic understanding of the capture process. Abstract : Supercapacitive swing adsorption (SSA) is a recently discovered electrochemically driven CO2 capture technology that promises significant efficiency improvements over traditional methods. A limitation of this approach is the relatively low CO2 adsorption capacity, and the underlying molecular mechanisms of SSA remain poorly understood, hindering optimization. Here we present a new device architecture for simultaneous electrochemical and gas-adsorption measurements, and use it to investigate the effects of charging protocols on SSA performance. We show that altering the voltage applied to charge the SSA device can significantly improve performance. Charging the gas-exposed electrode positively rather than negatively increases CO2 adsorption capacity and causes CO2 desorption rather than adsorption with charging. We also show that switching the voltage between positive and negative values further increases CO2 capacity. Previously proposed mechanisms of the SSA effect fail to explain these phenomena, so we present a new mechanism based on movement of CO2 -derived species into and out of electrode micropores. Overall, this work advances our knowledge of electrochemical CO2 adsorption by supercapacitors, potentially leading to devices with increased uptake capacity and efficiency.